2011
DOI: 10.1002/uog.8840
|View full text |Cite
|
Sign up to set email alerts
|

Four‐chamber view and ‘swing technique’ (FAST) echo: a novel and simple algorithm to visualize standard fetal echocardiographic planes

Abstract: Objective To describe a novel and simple algorithm (four-chamber view and 'swing technique' (FAST) echo) for visualization of standard diagnostic planes of fetal echocardiography from dataset volumes obtained with spatiotemporal image correlation (STIC) and applying a new display technology (OmniView). Methods Results In normal cases, the FAST echo algorithm (three locked lines and rotation of the five-chamber view on the y-axis) was able to generate the intended planes (longitudinal view of the ductal arch, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 78 publications
(74 reference statements)
2
36
0
Order By: Relevance
“…Multiplanar and/or VOCAL techniques have been used to assess different fetal structures such as lungs (Kalache et al 2003), placenta , gestational sac (Nardozza et al 2010b) and cerebellum (Rutten et al 2009). The main advantages of the VOCAL technique over the multiplanar technique are the shorter time needed to perform the Overall, median (range) sensitivity, specificity, positive and negative predictive values and falsepositive and -negative rates for identification of fetuses with CHD were 93% (77%-100%), 96% (84%-100%), 96% (83%-100%), 93% (79%-100%), 4.8% (2.7%-25%), and 6.8% (5%-22%), respectively; most frequent CHDs were conotruncal anomalies (36%); excellent intercenter agreement (k 5 0.97) Yeo et al (2011b) procedure (Ruano et al 2006b) and the minor corrections required on the external surface area at the end of the volume calculation process (Peralta et al 2006). Chang et al (2002c) estimated a time between 10 and 15 min to calculate the fetal upper-arm volume using the multiplanar mode with a 3.0-mm interval between slices.…”
Section: -Dus In Assessment Of Fetal Organ Volume and Estimation Of mentioning
confidence: 93%
See 1 more Smart Citation
“…Multiplanar and/or VOCAL techniques have been used to assess different fetal structures such as lungs (Kalache et al 2003), placenta , gestational sac (Nardozza et al 2010b) and cerebellum (Rutten et al 2009). The main advantages of the VOCAL technique over the multiplanar technique are the shorter time needed to perform the Overall, median (range) sensitivity, specificity, positive and negative predictive values and falsepositive and -negative rates for identification of fetuses with CHD were 93% (77%-100%), 96% (84%-100%), 96% (83%-100%), 93% (79%-100%), 4.8% (2.7%-25%), and 6.8% (5%-22%), respectively; most frequent CHDs were conotruncal anomalies (36%); excellent intercenter agreement (k 5 0.97) Yeo et al (2011b) procedure (Ruano et al 2006b) and the minor corrections required on the external surface area at the end of the volume calculation process (Peralta et al 2006). Chang et al (2002c) estimated a time between 10 and 15 min to calculate the fetal upper-arm volume using the multiplanar mode with a 3.0-mm interval between slices.…”
Section: -Dus In Assessment Of Fetal Organ Volume and Estimation Of mentioning
confidence: 93%
“…The volume can be sectioned freely by setting the ultrasound equipment to trace straight lines, curved lines or polylines, as selected on a menu. Omniniew or other commercially available software has the potential to facilitate the reconstruction and evaluation of 3-D volumes, thus compensating for limited operator expertise, and requires a short learning curve in training programs (Yeo et al 2011a(Yeo et al , 2011b. Tonni et al (2014) reported that accurate off-line volume data sets of the corpus callosum and the posterior fossa were accurately reconstructed from the sagittal and axial planes in 98.5% and 96% of cases, respectively, with agreement rates of 0.96 and 0.91 for the midsagittal and axial planes, respectively, in cases involving pathology (Fig.…”
Section: -D Ultrasound and The Study Of Fetal Brain Anatomy: ''The Nmentioning
confidence: 99%
“…More recently, OmniView (GE Medical Systems, Kretztechnik GmbH, Zipf, Austria), a new display modality in four-dimensional ultrasonography, has been used to develop an algorithm to image standard fetal echocardiographic planes by drawing four dissecting lines through the longitudinal view of the ductal arch contained in a STIC volume dataset. The authors reported that the 'swing technique' was able to generate the three vessels and trachea view, five-chamber view and/or long-axis view of the aorta, four-chamber view, and upper stomach view in all 50 fetuses without heart defects [63 ].…”
Section: Multiplanar Displaymentioning
confidence: 99%
“…The first line (yellow), the second line (fuchsia), and the third line (turquoise) should be applied to the region of interest, achieving non-orthogonal planes simultaneously displayed on 3D volume multiplanar rendering [6]. This technology has been applied in obstetrics to assess the fetal hard and soft palates [6], central nervous system [5], heart [7], and spine [8]. In gynecology, the OmniView® has been used to assess the location of intrauterine devices [9].…”
Section: Introductionmentioning
confidence: 99%